STUDI PERBANDINGAN KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE TAKE AND GIVE DAN THINK PAIR SQUARE DI KELAS XI IPA SMA NEGERI 1 REJANG LEBONG - Windy Novita Amalia; Hermansyah Amir; Sumpono Sumpono (University of Bengkulu, 2019)
The purpose of this research is to measure the difference of improvement of students' critical thinking ability by applying the cooperative model Take and give type with Think Pair Square type on salt hydrolysis material in grade XI IPA SMA Negeri 1 Rejang Lebong academic year 2017 / 2018. This study was conducted with a population of 201 students from 6 IPA classes and a sample of 68 students from 2 classes it class XI IPA 1 as experiment 1 and XI IPA 5 as experiment 2 which can be from normality and homogeneity test. The research is a kind of quasi experiment. Data analysis used is normality test, homogeneity test and hypothesis test. The students' critical thinking ability data is obtained from the pretest and posttest values at the beginning of the meeting and at the end of the meeting. This critical thinking skills test consists of 15 essay questions. The average increase in critical thinking skills for Take and give classes with Think Pair Square class is 44,757 and 51,683. By testing the hypothesis using t test with a significant level of 0.05, then obtained the value for t hitung> t table is 3.081> 1.668. The results showed that students' critical thinking skills with the classes that apply the Think Pair Square learning model is better than the class that applied the Take and give learning model.